2019
DOI: 10.1007/s11606-019-05489-3
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Diabetes and Severe Mental Illness: Outcomes in an Integrated Health Care Delivery System

Abstract: BACKGROUND: Diabetes prevalence is twice as high among people with severe mental illness (SMI) when compared to the general population. Despite high prevalence, care outcomes are not well understood. OBJECTIVE: To compare diabetes health outcomes received by people with and without comorbid SMI, and to understand demographic factors associated with poor diabetes control among those with SMI. DESIGN: Retrospective cohort study PARTICIPANTS: 269,243 adults with diabetes MAIN MEASURES: Primary outcomes included o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Studies had to meet the following inclusion criteria: report on the primary outcome measure of mammography screening, compare mammography screening rates to a control population of women meeting recommended breast cancer screening guideline criteria, and provide sufficient data to calculate relative-risk or odds ratios (ORs). As previously described, studies were eligible if they included women with a diagnosis of schizophrenia or a related psychotic disorder, such as schizoaffective disorder, as defined by DSM-5 (295.xx), ICD-10 (F20.x, F25.x), or other valid measure (20). We did not aim to analyze studies that reported mammography screening rates for women with mental distress, delirium, dementia, developmental disorders, eating disorders, nonpsychotic mood disorders, or substance use disorders.…”
Section: Eligibility Criteria and Study Selectionmentioning
confidence: 99%
“…Studies had to meet the following inclusion criteria: report on the primary outcome measure of mammography screening, compare mammography screening rates to a control population of women meeting recommended breast cancer screening guideline criteria, and provide sufficient data to calculate relative-risk or odds ratios (ORs). As previously described, studies were eligible if they included women with a diagnosis of schizophrenia or a related psychotic disorder, such as schizoaffective disorder, as defined by DSM-5 (295.xx), ICD-10 (F20.x, F25.x), or other valid measure (20). We did not aim to analyze studies that reported mammography screening rates for women with mental distress, delirium, dementia, developmental disorders, eating disorders, nonpsychotic mood disorders, or substance use disorders.…”
Section: Eligibility Criteria and Study Selectionmentioning
confidence: 99%
“…First, we performed a pre- and post-analysis of the time periods before and after the multicomponent strategies, adjusting for sex at birth, age as a continuous variable, race/ethnicity, housing status assessed at the beginning of SIP (experiencing homelessness/unstable housing vs housed; also assessed at the end of the analysis period), and the presence of severe mental illness based on International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10) codes [ 21 ], using mixed-effects logistic regression. A random effect was included for the participant over multiple laboratory assessments.…”
Section: Methodsmentioning
confidence: 99%
“…The co-occurrence of schizophrenia and Type II diabetes within Latino communities continues to provide challenges for those seeking to improve their physical and psychological health simultaneously. Recent work by Mangurian et al, 2020 indicates that co-occurrence of diabetes and any serious mental illness is higher in Latino communities and is less well controlled. Further complicating this issue and potentially perpetuating stigma in this area is fact that the primary medical treatment for schizophrenia, antipsychotic medication, significantly increases one’s risk of Type II diabetes (Hirsch et al, 2017 ; Neilson et al, 2010 ; Smith et al, 2008 ), potentially discouraging those with untreated psychotic symptoms from seeking care for these symptoms.…”
Section: Mental Health Stigmamentioning
confidence: 99%